PENGARUH PRODUK DOMESTIK REGIONAL BRUTO, UPAH MINIMUM, INFLASI DAN INVESTASI TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI NUSA TENGGARA BARAT TAHUN 2011-2020 - I Nyoman Sutama; U Usman; N Nunung (Jurnal Ekonomi & Bisnis, 2021)
This study aims to know the effect of the Gross Domestic Regional Product (PDRB), minimum wage, inflation and investment toward employment opportunity in West Nusa Tenggara Province. The data used in this study was time series data for 10 years from 2011 to 2020. The data sources used was secondary data obtained from the Central Bureau of Statistics and Department Of Investment and One Stop Service of West Nusa Tenggara Province. The analysis technique used was multiple linear regressions. The results of study showed that partially Gross Domestic Regional Product (PDRB) Minimum Wage and Inflation had effect toward employment opportunity in West Nusa Tenggara Province. Furthermore, Gross Domestic Regional Product (PDRB), minimum wage, inflation and investment simultaneously had effect toward employment opportunity in West Nusa Tenggara province. It was based the value of f-value of 8.504 > f-table of 5.19 with significance value of 0.019<0.05.The value of the coefficient of determination was 0.769, it means that the effect of Gross Domestic Regional Product (PDRB) Minimum Wage and Inflation toward employment opportunity was 76.9% while it remaining of 23.1% was effected by others variable out of this study.